Sequencing Bait: Nuclear and Mitogenome Assembly of an Abundant Coastal Tropical and Subtropical Fish, Atherinomorus stipes. (22nd July 2022) - Drown, Melissa K; DeLiberto, Amanda N; Flack, Nicole; Doyle, Meghan; Westover, Alexander G; Proefrock, John C; Heilshorn, Sandra; D'Alessandro, Evan; Crawford, Douglas L; Faulk, Christopher; Oleksiak, Marjorie F
Abstract: Genetic data from nonmodel species can inform ecology and physiology, giving insight into a species' distribution and abundance as well as their responses to changing environments, all of which are important for species conservation and management. Moreover, reduced sequencing costs and improved long-read sequencing technology allows researchers to readily generate genomic resources for nonmodel species. Here, we apply Oxford Nanopore long-read sequencing and low-coverage (∼1x) whole genome short-read sequencing technology (Illumina) to assemble a genome and examine population genetics of an abundant tropical and subtropical fish, the hardhead silverside ( Atherinomorus stipes ). These fish are found in shallow coastal waters and are frequently included in ecological models because they serve as abundant prey for commercially and ecologically important species. Despite their importance in sub-tropical and tropical ecosystems, little is known about their population connectivity and genetic diversity. Our A. stipes genome assembly is about 1.2 Gb with comparable repetitive element content (∼47%), number of protein duplication events, and DNA methylation patterns to other teleost fish species. Among five sampled populations spanning 43 km of South Florida and the Florida Keys, we find little population structure suggesting high population connectivity.